When Women Do Not Want It: Young Female Bargoers' Experiences With and Responses to Sexual Harassment in Social Drinking Contexts. (October 2017) - Graham, Kathryn; Bernards, Sharon; Abbey, Antonia; Dumas, Tara M.; Wells, Samantha
Women frequently experience unwanted sexual touching and persistent advances at bars and parties. This study explored women's responses to these unwanted experiences through online surveys completed by 153 female bargoers (aged 19-29) randomly recruited from a bar district. More than 75% had experienced sexual touching or persistence (46% both). Most women used multiple deterrent strategies, including evasion, facial expressions, direct refusals, aggression, friends' help, and leaving the premises. Women experienced negative feelings (disrespected, violated, disgusted, angry, embarrassed), especially from incidents involving touching. Cultural change is needed to reduce substantial negative impacts of sexual harassment on women in drinking and other settings.